Prenatal diagnosis of X-linked craniofrontonasal dysplasia: Case report - Quintana-Hernández, Daniel (2024)
Introduction: Craniofrontonasal dysplasia (CFND) is a rare malformation disorder that primarily affects the eyes, nose and forehead. Of all of them, hypertelorism is the main and invariable component. It occurs sporadically in most cases. Only a few cases diagnosed before birth have been reported in the literature. Objective: To describe a prenatally diagnosed case of X-linked craniofrontonasal dysplasia. Case presentation: A 21-year-old pregnant woman with initial evaluation of increased genetic risk of hereditary disease due to a personal and family history of DCFN. At 24 weeks of pregnancy, an ultrasound was performed at the Provincial Center for Medical Genetics of Mayabeque - Cuba, a confirmation consultation that described facial anomalies in a female fetus with hypertelorism, a wide nasal bridge and a half-open mouth maintained throughout the study. No facial clefts or other associated defects were reported. Genetic counseling was offered. Based on the background information obtained, the assessment of the prepared family tree and the reported ultrasound findings, it was concluded that it could correspond to a fetus affected by DCFN. The couple requested voluntary termination of the pregnancy. Fetal necropsy confirmed the diagnosis of DCFN. Conclusions: To make the prenatal diagnosis of DCFN, fetal ultrasound phenotyping, analysis of family history and anatomopathological findings are the key to personalized genetic counseling that allows the couple the reproductive option that they consider most appropriate.